2022
DOI: 10.1002/ejic.202200331
|View full text |Cite
|
Sign up to set email alerts
|

Front Cover: Manganese (III/IV) μ‐Oxo Dimers and Manganese (III) Monomers with Tetraaza Macrocyclic Ligands and Historically Relevant Open‐Chain Ligands (Eur. J. Inorg. Chem. 19/2022)

Abstract: The Front Cover shows how the discovery of manganese containing enzymes has prompted a range of synthetic small‐molecule complexes to be used as structural and functional mimics of the metalloenzyme chemistries. On the basis of this work, aza‐macrocyclic ligands have resulted in a small library of Mn(III) and bis μ‐oxo Mn(III)/Mn(IV) complexes, which built on the earlier work established with open‐chain ligand scaffolds. The characterization and structural information from these studies has now allowed studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
3
0
2
Order By: Relevance
“…The current situation, however, restricts our ability to comprehend the plausible pathway involved in the formation of 1 a / 2 a . Besides this, we have observed that 2 b over a period of time when left for crystallization results in the formation of a [(BPMEN*)Mn III (μ‐O) 2 Mn IV (BPMEN*)](ClO 4 ) 3 .2(CH 3 CN).1(H 2 O) dimer which is in accordance with the literature reports (Figures S26–S27, Tables S7–9) [40] …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The current situation, however, restricts our ability to comprehend the plausible pathway involved in the formation of 1 a / 2 a . Besides this, we have observed that 2 b over a period of time when left for crystallization results in the formation of a [(BPMEN*)Mn III (μ‐O) 2 Mn IV (BPMEN*)](ClO 4 ) 3 .2(CH 3 CN).1(H 2 O) dimer which is in accordance with the literature reports (Figures S26–S27, Tables S7–9) [40] …”
Section: Resultssupporting
confidence: 91%
“…Besides this, we have observed that 2 b over a period of time when left for crystallization results in the formation of a [(BPMEN*)Mn III (μ-O) 2 Mn IV (BPMEN*)](ClO 4 ) 3 .2(CH 3 CN).1(H 2 O) dimer which is in accordance with the literature reports (Figures S26-S27, Tables S7-9). [40] Since 1 and 2 were prolific in oxidizing thioethers into sulfoxides in substrates like thioanisoles, we anticipated the intracellular thiols could be highly sensitive to this high-valent metal-oxo species generated from 1 and 2. Maintenance of Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, numerous model complexes featuring bis(μoxo)dimanganese(III,IV) cores that serve as potential mimics of the Mn III Mn IV form of the class Ib RNRs have been synthesized. [12][13][14][15] Some of these complexes have been shown to oxidize substrates by a H-atom transfer mechanism, thus mimicking tyrosine oxidation by the Mn III Mn IV form of Mn-RNR. [13,16,17] However, the reported synthetic procedures generally require treatment of mononuclear Mn II complexes with O 2 or H 2 O 2 , which differs significantly from the proposed enzymatic mechanism involving the reaction between Mn II 2 cofactor and O 2 *À .…”
Section: Introductionmentioning
confidence: 99%
“…Entsprechend wurden zahlreiche Modellkomplexe mit Bis(μ-oxido)dimangan-(III,IV)-Kernen, die potentiell die Mn III Mn IV -Struktur der Class Ib RNRs nachahmen, synthetisiert. [12][13][14][15] Vergleichbar zur Tyrosin-Oxidation durch die Mn III Mn IV -Struktur in der Mn-RNR zeigten einige dieser Komplexe die Oxidation von Substraten über einen H-Atom-Transfer-Mechanismus. [13,16,17] [18] und [Mn II 2 (OAc) 2 (BPMP)](ClO 4 ) (BPMP = (2,6-Bis{[bis(2-pyridylmethyl)amino]methyl}-4-methylphenolat) [19]…”
Section: Introductionunclassified
“…Die Untersuchung der reaktiven und spektroskopischen Eigenschaften von biomimetischen Modellverbindungen kann wichtige Erkenntnisse bezüglich des Mechanismus von enzymatischen Reaktionen liefern. Entsprechend wurden zahlreiche Modellkomplexe mit Bis(μ‐oxido)dimangan(III,IV)‐Kernen, die potentiell die Mn III Mn IV ‐Struktur der Class Ib RNRs nachahmen, synthetisiert [12–15] . Vergleichbar zur Tyrosin‐Oxidation durch die Mn III Mn IV ‐Struktur in der Mn‐RNR zeigten einige dieser Komplexe die Oxidation von Substraten über einen H‐Atom‐Transfer‐Mechanismus [13, 16, 17] .…”
Section: Introductionunclassified